The relationship of entrepreneurial leadership with the development of competitive advantage in private schools in Jeddah from the perspective of teachers and educational supervisors - Al-Badri, Shaima Fayez; Hariri, Randa (Journal of Educational and Psychological Sciences, 2025)
The research aimed to reveal the relationship of entrepreneurial leadership to developing competitive advantage in private schools in Jeddah from the point of view of female teachers and educational supervisors, and the differences in the degree of practicing entrepreneurial leadership in private schools in Jeddah due to the variables (job title, academic qualification, experience, training courses). The study relied on the correlational survey classroom approachKeywords: entrepreneurial leadership, competitive advantage, private schools. The questionnaire was applied to a random sample that included 346 female teachers and 28 educational supervisors. The results showed that the entrepreneurial leadership of private school principals had an average of (3.85 out of 5), with a (large) degree, and the creativity dimension had an average of (3.88 out of 5), vision with an average of (3.85), risk-taking with an average of (3.84), and finally initiative with an average of (3.82). The level of competitive advantage has an average of (3.78 out of 5), with a rating of (large), and the dimension of responsiveness in the introduction has an average of (3.80), service excellence has an average of (3.79), and finally quality has an average of (3.76). There are no differences between the average degrees of practicing entrepreneurial leadership due to the difference in job title and qualification. There are differences between the average degrees of practicing entrepreneurial leadership due to the difference in the number of training courses in the direction of female teachers and supervisors who have (7-9) courses. There are no differences in the level of competitive advantage due to differences in job title and educational qualifications. Experience: For women with experience ranging from (11-15) years, there is a positive correlation between the degree of practicing entrepreneurial leadership and competitive advantage, and the correlation coefficient was (0.947).